Implementation of an interactive model for learning mathematics through games - Rodríguez Ortiz, Angélica María; Marín Ortiz, Claudia Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
A synthesis of the results of a research project are presented. In such study, a fast and functional prototype was designed and implemented on the basis of the Bridging Design Prototype [BDP] approach proposed by Gómez and Tamblyn. The BDP of an interactive model for learning the multiplication tables was incorporated into a second-grade group of primary school by carrying out activities involving both students and teachers inside the classroom. The study focused on analyzing how this prototype strengthens the development of mathematical thinking skills in children while they learn the tables through games. Rapid ethnography was the research method utilized in the study given that it allows for participant observation in mathematics instruction.